2022
DOI: 10.1161/atvbaha.121.316651
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial GNAQ p.R183Q Increases ANGPT2 (Angiopoietin-2) and Drives Formation of Enlarged Blood Vessels

Abstract: Objective: Capillary malformation (CM) occurs sporadically and is associated with Sturge-Weber syndrome. The somatic mosaic mutation in GNAQ (c.548G>A, p.R183Q) is enriched in endothelial cells (ECs) in skin CM and Sturge-Weber syndrome brain CM. Our goal was to investigate how the mutant Gαq (G-protein αq subunit) alters EC signaling and disrupts capillary morphogenesis. Approach and Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 80 publications
(127 reference statements)
1
50
0
Order By: Relevance
“…Recently, molecular investigations have found that human endothelial cells of CMs harboring the GNAQ p.R183Q variant lead to constitutive activation of phospholipase C (PLC), promoting the expression of proangiogenic downstream targets of the nuclear factor kappa B (NF‐κB) signaling pathway, most importantly angiopoietin‐2 (ANGPT2) 8 . ANGPT2 was shown to be a critical driver of vessel enlargement and distortion that may impact blood flow and permeability in blood vessels comprised of cells expressing GNAQ p.R183Q.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, molecular investigations have found that human endothelial cells of CMs harboring the GNAQ p.R183Q variant lead to constitutive activation of phospholipase C (PLC), promoting the expression of proangiogenic downstream targets of the nuclear factor kappa B (NF‐κB) signaling pathway, most importantly angiopoietin‐2 (ANGPT2) 8 . ANGPT2 was shown to be a critical driver of vessel enlargement and distortion that may impact blood flow and permeability in blood vessels comprised of cells expressing GNAQ p.R183Q.…”
Section: Discussionmentioning
confidence: 99%
“…Postzygotic variations in these genes have been implicated in dysregulated endothelial cell signaling. 7,8 We present a series of five patients with cutaneous CMs, postzygotic GNAQ/11 variants, and early-onset hypertension. We review possible mechanisms to explain the association between the development of CMs and early-onset hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional in vivo and in vitro complex studies like those performed by Huang et al are needed to advance our understanding of PWB. The authors in this study identified Angpt2 as a downstream factor increased by endothelial GNAQ p.R183Q signaling that caused vessel dilation; this feature was reversed through GNAQ inhibition using YM-254890 or shRNA knockdown of Angpt2 (Huang et al, 2022). Thorough studies that identify direct controllers of PWB vessel dysfunction are rare.…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…One such study revealed that GNAQ (R183Q) mutations modestly increased the activity of ERK. To further elucidate the underlying mechanism of GNAQ (R183Q) mutations, experiments on these types of mutations were performed in vitro and in vivo [ 52 ]. Endothelial colony-forming cell lines were transfected with lentivirus expressing p.R183Q GNAQ (EC-R183Q).…”
Section: Pathogenesismentioning
confidence: 99%